MEMBACA KEMBALI EKSISTENSI HUKUM ISLAM DALAM KERAGAMAN HIDUP DAN KEHIDUPAN - Aibak, Kutbuddin (IAIN Tulungagung, 2017)
Islamic law contains high elasticity which can be traced back from the principles of its decision making. The elasticity occurs because allah as the creator of the law does not take for granted all cases. Most of the nash embraces general principles and universal law. Nash which relates to partial specific cases are also open from broad interpretation and understanding, the utility of the law in its application and facility. As the results, many mujtahids never come to a single unanimous decision in viewing a case or problem.Keywords: The Existence of Islamic Law, Elasticity, Ijtihad